David Hare's Stuff Happens a dramatic journey of American war on Iraq - Kaur, Hardev,Salih, Elaff Ganim,Hassan, Mohamad Fleih (online, 2016)
Abstract: The war launched by America and its allies against the country of Iraq on 2003 was a debatable and notorious war for the public opinion was shocked with the realization that the reasons for launching the war under the title ‘Iraq’s Mass Destruction Weapons' were false. The tragic consequences of this war led many writers around the world to question the policy of the United States and its manipulation of facts to justify their narratives. The present study examines the American policy of invading Iraq in David Hare's Stuff Happens. It investigates Hare's technique of combining documentary realism with imaginative reconstruction of the arguments to dramatize the American Invasion of Iraq. Stuff Happens is a historical and political play written as a verbatim theatre. It depicts the backroom deals and political maneuvers of the Bush administration in justifying their campaign against the
10.18052/www.scipress.com/ILSHS.67.57
Keywords: (thesoz)USA; (thesoz)Irak; (thesoz)Krieg; (thesoz)Invasion; (thesoz)Wahrheit; (thesoz)Manipulation; (thesoz)Literatur; (thesoz)Theater; Verbatim Theater